Sistem Informasi Sekolah Berbasis Android di Sekolah SMA Negeri 1 Cepogo Kabupaten Boyolali - Lukmana, Dhefi Intan; Fatkhan Agus Setiawan; Fariyono; Wisnu Sanjaya (JITU, 2025)
Effective communication between schools, students, and parents is a crucial factor in supporting the success of the educational process. However, many schools still rely on informal communication platforms such as WhatsApp groups, which often lack structure and can lead to miscommunication. This study aims to design and develop InfoSekolah Cepogo, an Android-based application that delivers school information in a centralized, real-time manner according to user access rights. The research employs a system development method consisting of planning, implementation, and evaluation stages, using Black-Box Testing and User Testing techniques. Data were obtained through functional testing of the main features and questionnaires distributed to 30 respondents, consisting of students, teachers, and parents. The results show that the application runs stably on various Android devices, is user-friendly, and facilitates faster information delivery. Moreover, the application increases parental involvement in school activities. Several improvements were made based on user feedback, including the addition of automatic notification features and initial usage guides. Based on these findings, it can be concluded that InfoSekolah Cepogo is effective as a modern and functional school communication and information platform. Keywords: school application, digital communication, Black-Box Testing, User Testing.